PENGARUH MODIFIKASI NOKEN AS SUZUKI SATRIA F150 MENGGUNAKAN BEARING (NEEDLE ROLLER BEARING) TERHADAP PERUBAHAN TORSI DAN PUNCAK TENAGA (PEAK POWER) - Budiyono, Budiyono; Firmansyah, Aditya (Universitas Muhammadiyah Pekajangan Pekalongan, 2018)
ABSTRACT This modification aims to make the camshaft Suzuki Satria F150 standards just riveted on journals made from aluminum alloy, this journalized not use material bearing or no possible way so much friction. This modification process using the NTN bearing HK 1616 code before the paired bearing on the four ends of the camshaft first turner to 16 mm previously 22 mm in order to get into the shaft bearing . Holder on the size of the head 22 mm is the same as the size of the outside diameter is 22 mm bearing so it does not need to be changed, at the end of the shaft to the right contrived cover with a diameter of 22 mm as cover camshaft with stand head and given a 3 mm gap for track lubrication.Tests were carried out which changes the torque and peak power (peak power) before and after using the modified bearing by means of a variable dynometer with 5000 rpm to 11000 rpm. Keywordes :Camshaft, Bearing, Torque and Peak power